2019
DOI: 10.1126/sciadv.aaw4466
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen tension–mediated erythrocyte membrane interactions regulate cerebral capillary hyperemia

Abstract: The tight coupling between cerebral blood flow and neural activity is a key feature of normal brain function and forms the basis of functional hyperemia. The mechanisms coupling neural activity to vascular responses, however, remain elusive despite decades of research. Recent studies have shown that cerebral functional hyperemia begins in capillaries, and red blood cells (RBCs) act as autonomous regulators of brain capillary perfusion. RBCs then respond to local changes of oxygen tension (PO2) and regulate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…Wei et al (2016) provided evidence that the transient decrease in tissue O 2 tension resulting from neuronal-evoked increases in metabolic activity (Devor et al, 2011) increases red blood cell deformability and velocity in capillaries. The authors proposed that O 2 release-induced displacement of ankyrin from band 3 weakens spectrin-actin cytoskeleton interactions (Stefanovic et al, 2013;Zhou et al, 2019), thereby increasing erythrocytes deformability (Wei et al, 2016), a phenomenon later confirmed using both ex vivo (microfluidics) and in vivo (two-photon imaging) approaches (Zhou et al, 2019).…”
Section: Neurovascular Couplingmentioning
confidence: 95%
“…Wei et al (2016) provided evidence that the transient decrease in tissue O 2 tension resulting from neuronal-evoked increases in metabolic activity (Devor et al, 2011) increases red blood cell deformability and velocity in capillaries. The authors proposed that O 2 release-induced displacement of ankyrin from band 3 weakens spectrin-actin cytoskeleton interactions (Stefanovic et al, 2013;Zhou et al, 2019), thereby increasing erythrocytes deformability (Wei et al, 2016), a phenomenon later confirmed using both ex vivo (microfluidics) and in vivo (two-photon imaging) approaches (Zhou et al, 2019).…”
Section: Neurovascular Couplingmentioning
confidence: 95%
“…Specifically, the reversible association of deoxyHb with band 3 in the RBC membrane, increased intracellular glycolysis, and G i protein activation are all linked to this conformational change and have been shown to be required for deoxygenation-induced ATP release (Jagger et al 2001;Olearczyk et al 2004b;Chu et al 2016). In addition, the association of deoxyHb with band 3 increases RBC deformability by displacing band 3 from the cytoskeletal protein ankyrin (Stefanovic et al 2013;Chu et al 2016;Zhou et al 2019), which is closely associated with deoxygenation-induced increases in RBC capillary velocity (Zhou et al 2019), and also facilitates an increase in glycolysis by displacing a complex of glycolytic enzymes from band 3 (Campanella et al 2005(Campanella et al , 2008Chu & Low, 2006;Lewis et al 2009;Puchulu-Campanella et al 2013;Chu et al 2016). Increases in intracellular ATP also produce fluctuations, or 'flickering' , of the RBC membrane (Park et al 2010), which could activate mechanosensitive proteins such as G i proteins or Piezo1 channels (Gudi et al 1998;Cinar et al 2015) and facilitate the subsequent release of ATP.…”
Section: Mechanisms Of Impaired Deoxygenation-induced Atp Release Fromentioning
confidence: 99%
“…Spatial compartmentalization of processes and resources in RBCs was discovered (Hoffman et al, 2009;Chu et al, 2012). Complex dynamics precise orchestration of processes occurring in the circulating RBCs in response to the changes in micro-and macro-environment (hormonal and mechanical stimulation, changes in local or ambient oxygen availability, temperature, circadian rhythm-related processes and others) is becoming evident (e.g., O'Neill and Reddy, 2011;Cahalan et al, 2015;Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%